Krakow as the capital of the General Government. Consequences of hosting the Nazi-German authorities for a life of the city - Drozdowski, Mateusz (City and War, 2021)
Aim of the article is to analyze a specific situation of Krakow during the Nazi-German occupation, when the city played a role of a capital of the General Government. The city functioned under a typical occupation regime, however, at the same time it was a seat of the authorities. As a result thousands of German functionaries and their families settled in Krakow. It had significant impact on many aspects of functioning of Krakow, ranging from social and housing issues, through architecture, economy, methods of extermination of the Jewish population and finally organization of the Polish underground. A separate issue discussed in the article are the Nazi propaganda campaigns conducted mainly in Krakow. Due to limitations, all these issues are presented in a general way, nevertheless giving a picture of specificity of Krakow’s war experience. Author indicates that the fate of the city is not typical for the Polish lands occupied by the Third Reich. Contradictory to the other places, Krakow was not only a city that was conquered and controlled, but we can see it as a beginning of a new, colonial, Nazi order in the Eastern Europe.